Loss of p27 Associated with Risk for Endometrial Carcinoma Arising in the Setting of Obesity - McCampbell, A.S.; Mittelstadt, M.L.; Dere, R.; Kim, S.; Zhou, L.; Djordjevic, B.; Soliman, P.T.; Zhang, Q.; Wei, C.; Hursting, S.D.; Lu, K.H.; Broaddus, R.R.; et al. (Current Molecular Medicine, 2016)
Endometrial carcinoma (EC) exhibits the strongest association with obesity of all cancers. Growth of these tumors is driven by PI3K/AKT activation, and opposed by tumor suppressors, including the tuberous sclerosis complex 2 (TSC-2) and p27, with inactivation of TSC2 and loss or cytoplasmic mislocalization of p27 both being linked to PI3K/AKT activation. However, little is known about the involvement of p27 in the development of EC arising in the setting of obesity, especially its role early in disease progression. Using a panel of EC cell lines, in vitro studies using PI3K inhibitors provided evidence that p27 rescue contributes to the efficacy of interventions that inhibit endometrial cell growth. In
Keywords: p27